Roles of Nutrient Limitation on Western Lake Erie CyanoHAB Toxin Production - Malcolm A. Barnard; Justin D. Chaffin; Haley E. Plaas; Gregory L. Boyer; Bofan Wei; Steven W. Wilhelm; Karen L. Rossignol; Jeremy S. Braddy; George S. Bullerjahn; Thomas B. Bridgeman; Timothy W. Davis; Jin Wei; et al. (Toxins, 2021)
Cyanobacterial harmful algal bloom (CyanoHAB) proliferation is a global problem impacting ecosystem and human health. Western Lake Erie (WLE) typically endures two highly toxic CyanoHABs during summer: a Microcystis spp. bloom in Maumee Bay that extends throughout the western basin, and a Planktothrix spp. bloom in Sandusky Bay. Recently, the USA and Canada agreed to a 40% phosphorus (P) load reduction to lessen the severity of the WLE blooms. To investigate phosphorus and nitrogen (N) limitation of biomass and toxin production in WLE CyanoHABs, we conducted in situ nutrient addition and 40% dilution microcosm bioassays in June and August 2019. During the June Sandusky Bay bloom, biomass production as well as hepatotoxic microcystin and neurotoxic anatoxin production were N and P co-limited with microcystin production becoming nutrient deplete under 40% dilution. During August, the Maumee Bay bloom produced microcystin under nutrient repletion with slight induced P limitation under 40% dilution, and the Sandusky Bay bloom produced anatoxin under N limitation in both dilution treatments. The results demonstrate the importance of nutrient limitation effects on microcystin and anatoxin production. To properly combat cyanotoxin and cyanobacterial biomass production in WLE, both N and P reduction efforts should be implemented in its watershed.